Ceɗɗo, Sòfa, Tirailleur: slave status and military identity in nineteenth-century Senegambia. (3rd July 2018) - Westwood, Sarah Davis
ABSTRACT: This article outlines the historical evolution of military recruitment in the Senegambia region. From the seventeenth through the nineteenth century, French military officers benefited from indigenous modes of conscription, recruitment, and training, employing the services of slave caste men and professional soldiers. It was only through a co-optation of local strategies, first through the procurement of military aid from slave-owning elites and later the offer to purchase enslaved men from local nobility and pay ceɗɗo and sòfa warriors, that the French were able to build the West African military force known as the tirailleurs sénégalais .